UNVEILING A NEW PARADIGM: EXPLORING INNOVATIVE STRATEGIES IN COMMUNITY PREFERENCES FOR FOOD SECURITY PROGRAMS AND STRENGTHENING LOCAL ECONOMY - andik pratama; Juwita P. R.Suwondo; Endah Ayu N. L. N; Iroh Maharani (Jurnal Ekonomi, 2023)
Through the implementation of the categorical analysis method Probit, the research aims to analytically examine the preference model of the Karangwidoro Village community through the dimension of participation probability in the food security program initiative, as well as to formulate a model approach strategy aimed at revitalizing community motivation factors. The results indicate that distance influences community motivation to participate in the food security program, and there are methods of approach to encourage community motivation, namely through the SSA and ZOPP methods.